1979
DOI: 10.1073/pnas.76.3.1164
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase of mouse teratoma stem cells: Immunochemical and structural evidence for its identity as a somatic gene product

Abstract: The immunochemical and structural characteristics of the alkaline phosphatase [orthophosphoric-monoester phosphohydrolase (alkaline optimum), EC 3.1.3.1] from mouse teratoma stem cells derived from the teratoma (ascitic and solid tumors and the F9 and PCC4 cell lines) have been compared to those of the alkaline phosphatases expressed in normal mouse placenta and several adult organs. Crossreactivity of the stem celalkaline phosphatase with antisera reacting with placental, kidney, liver, and brain alkaline ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…T h e results also den]-onstrated that the induction of APase was not due to a few cells with higher than normal activities, but rather was caused by a n increase in the relative proportion of cells with higher activities. This is consistent with the data showing that APase is not a gene product unique to the E C cells (9) and that RrdUrd induced APase in several nonteratocarcinoma cell lines (4, 2 3 ) . T h e mechanism of induction of AI'ase is possibly fundamentally different from the extinction of differential gene function in other systems.…”
Section: Discussionsupporting
confidence: 92%
“…T h e results also den]-onstrated that the induction of APase was not due to a few cells with higher than normal activities, but rather was caused by a n increase in the relative proportion of cells with higher activities. This is consistent with the data showing that APase is not a gene product unique to the E C cells (9) and that RrdUrd induced APase in several nonteratocarcinoma cell lines (4, 2 3 ) . T h e mechanism of induction of AI'ase is possibly fundamentally different from the extinction of differential gene function in other systems.…”
Section: Discussionsupporting
confidence: 92%
“…Most tissues in the body have alkaline phosphatase activity and some tissues such as kidney, liver, and bone have increased levels of alkaline phosphatase. Previous studies have reported reactivity of antibodies directed against the specific alkaline phosphatase found in embryonic stem cells with many adult cell types, demonstrating the non-specific nature of this assay [33]. Although alkaline phosphatase staining can provide supportive evidence that cells are in a pluripotent state, it is not specific or definitive.…”
Section: Characterization Of Es/ips Cells and Evaluation Of Pluripotencymentioning
confidence: 97%
“…ALP enzyme has a dimeric structure capable of binding Zn 2+ and Mg 2+ ions at different sites to stimulate or inhibit its catalytic reaction. In humans, four forms of ALP cDNA have been cloned: one of them is widely distributed (liver, bone, kidney) [6, 7], one restricted to the intestine [8], one to the placenta [9], and one restricted to teratomas and germ cells [10]. ALP hydrolyzes phosphate groups and its activity is involved in a broad range of essential physiological and pathological processes.…”
Section: Introductionmentioning
confidence: 99%